FRACTOGRAPHY ANALYSIS OF Al6061 UNDER FATIGUE SPECTRUM LOADINGS - Zakaria, Kamarul Ariffin (2012)
This paper discusses the fractography observation in crack propagations of Al6061 under a fatigue spectrum loading. Most of the real components and engineering structures are subjected to stress of variable amplitude. The load sequences in variable amplitude loading condition can have a very significant effect on the fatigue crack propagation rate. Fatigue crack propagation tests were performed according to ASTM E647 standard using a 100 kN servo-hydraulic fatigue testing machine. Random loading signals were obtained from the engine mount bracket of an automobile while driven at almost constant velocity onto different surface conditions, i.e. on the residential area and highway road. These random loadings were converted to constant amplitude loading (CAL), high to low and low to high spectrum loadings in order to study the effect of loading sequence on the crack propagation rates. The fatigue fracture surfaces were then analysed using a high magnifying tabletop microscope to identify the fracture behaviour under particular load sequences. Results showed that the fatigue fractography behaviours were influenced significantly by the load interaction and the sequence effect, which can be related to the crack propagation rate of Al6061 under fatigue spectrum loadings.